Renewable energy power generation: a policy review pertaining to wind energy in India. (2017) - Kulkarni, Sanjeev H.; Anil, T.R.
Energy used to be produced mostly from fossil fuels until the near past, and the use of these fuels has created many environmental problems. For this reason, renewable energy resources have become important for energy production. Worldwide, about 86.4% of energy is produced by fossil fuels. Renewable energy has become an important agenda of India's energy planning process especially since climate change has taken centre stage in the domestic and international policy arena. To demonstrate its commitment to renewable energy, the government has set aggressive targets for renewables and several incentives and policy initiatives at the central and state levels have been put in place both for grid connected and off-grid renewable energy. An increasing tendency to use renewable energy resources in the world has revealed a need to study the current position of wind energy also and particularly the policies to increase the usage of wind energy. Wind energy provides a cost-effective and scalable alternative to conventional energies. The focus of this paper is on evaluating the effectiveness of policies with respect to deployment of renewable energy sources and in particular wind energy in India.